The OECD model convention-1997 and beyond : current problems of the permanent establishment definition : proceedings of a seminar held in new Delhi, in 1997 during the 51st Congress of the International Fiscal Association /: current problems of the permanent establishment definition : proceedings of a seminar held in new Delhi, in 1997 during the 51st Congress of the International Fiscal Association. (2016) - Unknown
No abstract available